Electrolysis cell

The electrolytic cell design addresses gas diffusivity and structural integrity issues by using a 100 μm thick gas diffusion layer with a ±0.05% dimensional change rate, enhancing gas diffusivity and preventing damage to the electrolyte and hydrogen electrode layers.

JP2025007030APending Publication Date: 2025-01-17NGK INSULATORS LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023108159
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing electrolytic cells face issues with gas diffusivity in the bonding layer, leading to potential warping and damage to the electrolyte and hydrogen electrode layers due to the reduction of NiO to Ni during heat treatment.

Method used

The electrolytic cell design includes a gas diffusion layer made of NiO and ceramic material, with a thickness of 100 μm or more, and a dimensional change rate of ±0.05% after reduction treatment, ensuring improved gas diffusivity and minimizing damage to the electrolyte and hydrogen electrode layers.

Benefits of technology

The solution enhances gas diffusivity while preventing warping and peeling or cracking in the electrolytic cell, maintaining structural integrity and improving electrode reaction uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007030000001_ABST
    Figure 2025007030000001_ABST
Patent Text Reader

Abstract

To provide an electrolysis cell capable of both improving the gas diffusivity of a gas diffusion layer and suppressing damage to an electrolyte layer and a hydrogen electrode layer.SOLUTION: There is provided an electrolysis cell 1 having a metal support 10 and a cell body part 20. The metal support 10 has a plurality of communication holes 11 formed on a first main surface 12. The cell body part 20 has a gas diffusion layer 5 covering the plurality of communication holes 11, a hydrogen electrode layer 6 disposed on the gas diffusion layer 5, an oxygen electrode layer 9, and an electrolyte layer 7 disposed between the hydrogen electrode layer 6 and oxygen electrode layer 9. The gas diffusion layer 5 is composed of NiO and a ceramic material. The thickness of the gas diffusion layer 5 is 100 μm or more. When the dimension of the gas diffusion layer 5 at room temperature in a reduced state obtained by subjecting the gas diffusion layer 5 to heat treatment in a reducing atmosphere at 750°C is defined as L2 and the dimension of the gas diffusion layer 5 at room temperature in a non-reduced state is defined as L1 and the amount of change is defined as ΔL=L2-L1, (ΔL / L1)×100 is within ±0.05%.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrolysis cell. [Background technology]

[0002] 2. Description of the Related Art Metal support type electrolysis cells having a cell body disposed on a metal support are known (see, for example, Patent Document 1).

[0003] The cell body of Patent Document 1 has a bonding layer, a hydrogen electrode layer, an electrolyte layer, and an oxygen electrode layer. The bonding layer covers a plurality of communication holes formed on the main surface of the metal support. The bonding layer is made of nickel oxide (NiO) and a ceramic material. The hydrogen electrode layer is disposed between the bonding layer and the electrolyte layer. The electrolyte layer is disposed between the hydrogen electrode layer and the oxygen electrode layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2021 / 221052 Summary of the Invention [Problem to be solved by the invention]

[0005] Patent Document 1 does not consider the gas diffusivity within the bonding layer, nor does it mention the thickness of the bonding layer. However, in order to increase the gas diffusivity within the bonding layer, it is preferable to make the bonding layer thicker.

[0006] Here, in order to impart electronic conductivity to the bonding layer (hereinafter referred to as the "gas diffusion layer"), if a heat treatment (hereinafter referred to as the "reduction treatment") is performed by supplying a reducing gas at high temperature to reduce the NiO contained in the gas diffusion layer to Ni, the electrolytic cell may warp and the electrolyte layer and hydrogen electrode layer may be damaged (peeling or cracking).

[0007] As a result of extensive investigations, the present inventors have found that the thickness of the gas diffusion layer and the rate of dimensional change of the gas diffusion layer caused by the reduction treatment have a significant effect on the warping of the electrolysis cell.

[0008] An object of the present invention is to provide an electrolysis cell capable of improving the gas diffusibility of the gas diffusion layer while suppressing damage to the electrolyte layer and the hydrogen electrode layer. [Means for solving the problem]

[0009] The electrolysis cell according to the first aspect of the present invention includes a metal support and a cell body. The metal support has a plurality of through holes formed on a main surface. The cell body has a gas diffusion layer formed on the main surface and covering the plurality of through holes, a hydrogen electrode layer disposed on the gas diffusion layer, an oxygen electrode layer, and an electrolyte layer disposed between the hydrogen electrode layer and the oxygen electrode layer. The gas diffusion layer is made of NiO and a ceramic material. The gas diffusion layer has a thickness of 100 μm or more. When the dimension of the gas diffusion layer in a reduced state obtained by subjecting the gas diffusion layer to a heat treatment in a reducing atmosphere at 750° C. is L2 at room temperature, and the dimension of the gas diffusion layer in a non-reduced state not subjected to the heat treatment is L1 at room temperature, the amount of change is ΔL=L2-L1, where (ΔL / L1)×100 is within ±0.05%.

[0010] The electrolysis cell according to a second aspect of the present invention is related to the above-mentioned first aspect, wherein the gas diffusion layer has a thickness of 450 μm or less.

[0011] An electrolysis cell according to a third aspect of the present invention is related to the first or second aspect, wherein the gas diffusion layer contains yttria as the ceramic material. Effect of the Invention

[0012] According to the present invention, it is possible to provide an electrolysis cell that can improve the gas diffusibility of the gas diffusion layer while suppressing damage to the electrolyte layer and the hydrogen electrode layer. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a cross-sectional view of an electrolysis cell according to an embodiment. [Diagram 2] FIG. 2 is a graph showing the relationship between the thickness of the gas diffusion layer and the curvature of the electrolysis cell when the dimensional change rate of the gas diffusion layer due to the reduction treatment is negative. [Diagram 3] FIG. 3 is a graph showing the relationship between the thickness of the gas diffusion layer and the curvature of the electrolysis cell when the dimensional change rate of the gas diffusion layer due to the reduction treatment is positive. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] (Electrolysis cell 1) 1 is a cross-sectional view of an electrolysis cell 1 according to an embodiment. The electrolysis cell 1 is a so-called metal support type electrolysis cell.

[0015] As shown in FIG. 1, the electrolysis cell 1 includes a metal support 10, a cell main body 20, and a flow path member 30.

[0016] [Metal support 10] The metal support 10 supports the cell main body 20. The metal support 10 is formed in a plate shape. The metal support 10 may be in the shape of a flat plate or a curved plate.

[0017] The metal support 10 is not particularly limited as long as it can support the electrolytic cell 1, and the thickness thereof can be, for example, 0.1 mm or more and 2.0 mm or less.

[0018] The metal support 10 has a plurality of communicating holes 11 , a first main surface 12 and a second main surface 13 .

[0019] Each communication hole 11 penetrates the metal support 10 from the first main surface 12 to the second main surface 13. Each communication hole 11 opens to each of the first main surface 12 and the second main surface 13. The opening of each communication hole 11 on the first main surface 12 side is covered by a gas diffusion layer 5 described later. The opening of each communication hole 11 on the second main surface 13 side is connected to a flow path 30a described later.

[0020] Each communication hole 11 can be formed by mechanical processing (for example, punching), laser processing, chemical processing (for example, etching), or the like.

[0021] In this embodiment, each communication hole 11 is formed linearly along the Z-axis direction. However, each communication hole 11 may be inclined with respect to the Z-axis direction, and may not be linear. The Z-axis direction refers to a direction perpendicular to the first main surface 12.

[0022] The first main surface 12 is provided on the opposite side to the second main surface 13. A cell main body 20 is disposed on the first main surface 12. A flow path member 30 is bonded to the second main surface 13.

[0023] The opening ratio of the plurality of communicating holes 11 in the first main surface 12 is preferably 5% or more. This allows the source gas to be uniformly supplied to the hydrogen electrode layer 6 (described later) through the communicating holes 11 and the gas diffusion layer 5, thereby making the electrode reaction field in the hydrogen electrode layer 6 uniform. As a result, the current density in the hydrogen electrode layer 6 can be increased.

[0024] The aperture ratio is calculated by dividing the total open area of ​​the plurality of communication holes 11 in a plan view of the first main surface 12 by the area of ​​the region of the first main surface 12 covered by the hydrogen electrode layer 6.

[0025] The metal support 10 is made of a metal material. For example, the metal support 10 is made of an alloy material containing Cr (chromium). Examples of such metal materials include Fe-Cr alloy steel (stainless steel, etc.) and Ni-Cr alloy steel. The Cr content of the metal support 10 is not particularly limited, but can be set to 4% by mass or more and 30% by mass or less.

[0026] The metal support 10 may contain Ti (titanium) and / or Al (aluminum). The Ti content in the metal support 10 is not particularly limited, but may be 0.01 mol% or more and 1.0 mol% or less. The Al content in the metal support 10 is not particularly limited, but may be 0.01 mol% or more and 0.4 mol% or less. The metal support 10 may contain Ti as TiO2 (titania) or Al as Al2O3 (alumina).

[0027] The metal support 10 may have an oxide film on its surface, which is formed by oxidation of the constituent elements of the metal support 10. A typical example of the oxide film is a chromium oxide film. The chromium oxide film covers at least a portion of the surface of the metal support 10. The chromium oxide film may also cover at least a portion of the inner wall surface of each of the communicating holes 11.

[0028] [Cell body 20] The cell body 20 is disposed on the metal support 10. The cell body 20 is supported by the metal support 10. The cell body 20 has a gas diffusion layer 5, a hydrogen electrode layer 6 (cathode), an electrolyte layer 7, a reaction prevention layer 8, and an oxygen electrode layer 9 (anode).

[0029] The gas diffusion layer 5, hydrogen electrode layer 6, electrolyte layer 7, reaction prevention layer 8, and oxygen electrode layer 9 are laminated in this order in the Z-axis direction from the metal support 10 side. The gas diffusion layer 5, hydrogen electrode layer 6, electrolyte layer 7, and oxygen electrode layer 9 are essential components, while the reaction prevention layer 8 is optional.

[0030] [Gas diffusion layer 5] The gas diffusion layer 5 is formed on the first main surface 12 of the metal support 10. The gas diffusion layer 5 is disposed between the metal support 10 and the hydrogen electrode layer 6. The gas diffusion layer 5 covers a plurality of communication holes 11 formed in the first main surface 12. A portion of the gas diffusion layer 5 may extend into each communication hole 11 of the metal support 10.

[0031] The gas diffusion layer 5 is made of nickel oxide (NiO) and a ceramic material.

[0032] Ni contained in the gas diffusion layer 5 exists in the form of NiO in an oxidizing atmosphere, and exists in the form of metallic nickel (Ni) in a reducing atmosphere. In a reducing atmosphere, Ni functions as an electron conductive material. In a reducing atmosphere, the gas diffusion layer 5 preferably has higher electron conductivity than the hydrogen electrode layer 6.

[0033] The ceramic material contained in the gas diffusion layer 5 may or may not have oxygen ion conductivity. Examples of the ceramic material that can be used include yttria (Y2O3), yttria stabilized zirconia (YSZ), calcia stabilized zirconia (CSZ), scandia stabilized zirconia (ScSZ), gadolinium doped ceria (GDC), samarium doped ceria (SDC), (La,Sr)(Cr,Mn)O3, (La,Sr)TiO3, Sr2(Fe,Mo)2O6, (La,Sr)VO3, (La,Sr)FeO3, LDC (lanthanum doped ceria), LSGM (lanthanum gallate), and a mixed material of two or more of these.

[0034] The volume ratio of NiO to the entire volume of the gas diffusion layer 5 (excluding the volume of the space occupied by the pores) can be 35 volume % or more and 55 volume % or less, calculated as Ni. The volume ratio of the ceramic material to the entire volume of the gas diffusion layer 5 (excluding the volume of the space occupied by the pores) can be 45 volume % or more and 65 volume % or less. The volume ratios of NiO and the ceramic material are measured in a non-reduced state that has not been subjected to the reduction treatment described below.

[0035] The thickness of the gas diffusion layer 5 is 100 μm or more. This improves the gas diffusibility of the gas diffusion layer 5, and therefore the raw material gas can be uniformly supplied to the hydrogen electrode layer 6. As a result, the electrode reaction field in the hydrogen electrode layer 6 becomes uniform, and the current density in the hydrogen electrode layer 6 can be increased.

[0036] The upper limit of the thickness of the gas diffusion layer 5 is not particularly limited, but may be 600 μm or less. The thickness of the gas diffusion layer 5 is preferably 450 μm or less. This makes it possible to reduce the amount of Ni contained in the gas diffusion layer 5, thereby reducing the manufacturing cost of the electrolysis cell 1.

[0037] The thickness of the gas diffusion layer 5 is calculated by the following method. First, the cross section of the gas diffusion layer 5 and the hydrogen electrode layer 6 along the Z-axis direction is exposed. Next, a backscattered electron image of the cross section is obtained at 3000 times magnification using an SEM device (FE-SEM JSM-7900F manufactured by JEOL Ltd.). Next, the part displayed in black in the backscattered electron image (corresponding to the pores) is identified using image analysis software Image-Pro manufactured by MEDIACYBERNETICS. Next, the line on the backscattered electron image where the porosity changes significantly is set as the boundary between the gas diffusion layer 5 and the hydrogen electrode layer 6. Next, the thickness of the gas diffusion layer 5 is measured on three lines perpendicular to the first main surface 12 of the metal support 10 on the backscattered electron image. Next, the thickness of the gas diffusion layer 5 is calculated by arithmetically averaging the thicknesses measured on the three lines.

[0038] The gas diffusion layer 5 is a porous body having gas diffusibility. The gas diffusion layer 5 allows the source gas to permeate to the hydrogen electrode layer 6 side. The gas diffusion layer 5 allows the product gas generated inside the hydrogen electrode layer 6 to permeate to the communication hole 11 side.

[0039] The porosity of the gas diffusion layer 5 is not particularly limited, but can be, for example, 10% to 40% in a non-reduced state described below. The porosity of the gas diffusion layer 5 is preferably 16% or more in a non-reduced state. This can further improve the gas diffusibility of the gas diffusion layer 5, allowing the raw material gas to be supplied more uniformly to the hydrogen electrode layer 6. As a result, the electrode reaction field in the hydrogen electrode layer 6 becomes more uniform, allowing the current density in the hydrogen electrode layer 6 to be further increased.

[0040] The porosity of the gas diffusion layer 5 is calculated by the following method. First, a cross section of the gas diffusion layer 5 along the Z-axis direction is exposed. Next, a backscattered electron image of the cross section of the gas diffusion layer 5 is obtained at 3000 times magnification using an SEM device (FE-SEM JSM-7900F, manufactured by JEOL Ltd.). Next, the parts displayed in black in the backscattered electron image (corresponding to pores) are identified using image analysis software Image-Pro manufactured by MEDIACYBERNETICS. Then, the total area of ​​the pores is divided by the total area of ​​the backscattered electron image of the gas diffusion layer 5 to calculate the porosity of the gas diffusion layer 5.

[0041] The method for forming the gas diffusion layer 5 is not particularly limited, and may be a firing method, a spray coating method (such as a thermal spray method, an aerosol deposition method, an aerosol gas deposition method, a powder jet deposition method, a particle jet deposition method, or a cold spray method), a PVD method (such as a sputtering method or a pulsed laser deposition method), or a CVD method.

[0042] The detailed configuration regarding the reduction treatment of the gas diffusion layer 5 will be described later.

[0043] [Hydrogen electrode layer 6] The hydrogen electrode layer 6 is disposed on the gas diffusion layer 5. The hydrogen electrode layer 6 is disposed between the gas diffusion layer 5 and the electrolyte layer .

[0044] The source gas is supplied to the hydrogen electrode layer 6 from each of the communication holes 11 via the gas diffusion layer 5. The source gas contains at least H2O.

[0045] When the raw material gas contains only H2O, the hydrogen electrode layer 6 produces H2 from the raw material gas in accordance with the electrochemical reaction of water electrolysis shown in the following formula (1).

[0046] Hydrogen electrode layer 6: H2O+2e - →H2+O 2- (1)

[0047] When the raw material gas contains CO in addition to H2O, the hydrogen electrode layer 6 converts H2, CO, and O2 from the raw material gas in accordance with the co-electrochemical reactions shown in the following formulas (2), (3), and (4). 2- Generate.

[0048] Hydrogen electrode layer 6: CO2+H2O+4e - →CO+H2+2O 2- (2) Electrochemical reaction of H2O: H2O+2e - →H2+O 2- (3) Electrochemical reaction of CO2: CO2+2e - →CO+O 2- (4)

[0049] The hydrogen electrode layer 6 contains NiO and an oxygen ion conductive material. Ni functions as an electron conductive material and also functions as a catalyst for promoting the electrochemical reaction of water electrolysis or co-electrolysis. As the oxygen ion conductive material, YSZ, CSZ, ScSZ, GDC, SDC, and a mixed material of two or more of these can be used. The hydrogen electrode layer 6 preferably has higher oxygen ion conductivity than the gas diffusion layer 5.

[0050] The volume ratio of NiO to the entire volume of the hydrogen electrode layer 6 (excluding the volume of the space occupied by the pores) can be 35 volume % or more and 55 volume % or less, calculated as Ni. The volume ratio of the ceramic material to the entire volume of the hydrogen electrode layer 6 (excluding the volume of the space occupied by the pores) can be 45 volume % or more and 65 volume % or less. The volume ratios of NiO and the ceramic material are measured in a non-reduced state that has not been subjected to the reduction treatment described below.

[0051] The thickness of the hydrogen electrode layer 6 is not particularly limited, but may be, for example, 5 μm or more and 30 μm or less. The hydrogen electrode layer 6 is thinner than the gas diffusion layer 5.

[0052] The porosity of the hydrogen electrode layer 6 is not particularly limited, but can be, for example, 10% or more and 30% or less in a non-reduced state described later.

[0053] The porosity of the hydrogen electrode layer 6 is calculated in the same manner as the porosity of the gas diffusion layer 5 described above.

[0054] The method for forming the hydrogen electrode layer 6 is not particularly limited, and may be a firing method, a spray coating method (such as a thermal spray method, an aerosol deposition method, an aerosol gas deposition method, a powder jet deposition method, a particle jet deposition method, or a cold spray method), a PVD method (such as a sputtering method or a pulsed laser deposition method), or a CVD method.

[0055] [Electrolyte layer 7] The electrolyte layer 7 is disposed between the hydrogen electrode layer 6 and the oxygen electrode layer 9. In this embodiment, the reaction prevention layer 8 is disposed between the electrolyte layer 7 and the oxygen electrode layer 9, so that the electrolyte layer 7 is sandwiched between the hydrogen electrode layer 6 and the reaction prevention layer 8.

[0056] The electrolyte layer 7 covers the hydrogen electrode layer 6 and also covers a region of the first main surface 12 of the metal support 10 that is exposed from the hydrogen electrode layer 6 .

[0057] The electrolyte layer 7 is formed by discharging the O 2- to the oxygen electrode layer 9. The electrolyte layer 7 is made of a dense material having oxide ion conductivity. The electrolyte layer 7 can be made of, for example, YSZ (yttria-stabilized zirconia, e.g., 8YSZ), GDC (gadolinium-doped ceria), ScSZ (scandia-stabilized zirconia), SDC (samarium-doped ceria), LSGM (lanthanum gallate), or the like.

[0058] The porosity of the electrolyte layer 7 is not particularly limited, but may be, for example, 0.1% to 7%. The thickness of the electrolyte layer 7 is not particularly limited, but may be, for example, 1 μm to 100 μm.

[0059] The method for forming the electrolyte layer 7 is not particularly limited, and a baking method, a spray coating method, a PVD method, a CVD method, or the like can be used.

[0060] [Reaction prevention layer 8] The reaction prevention layer 8 is disposed between the electrolyte layer 7 and the oxygen electrode layer 9. The reaction prevention layer 8 is disposed on the opposite side of the electrolyte layer 7 to the hydrogen electrode layer 6. The reaction prevention layer 8 prevents the constituent elements of the electrolyte layer 7 from reacting with the constituent elements of the oxygen electrode layer 9 to form a layer with high electrical resistance.

[0061] The reaction prevention layer 8 is made of an oxide ion conductive material, and may be made of GDC, SDC, or the like.

[0062] The porosity of the reaction prevention layer 8 is not particularly limited, but may be, for example, 0.1% to 50%. The thickness of the reaction prevention layer 8 is not particularly limited, but may be, for example, 1 μm to 50 μm.

[0063] The method for forming the reaction prevention layer 8 is not particularly limited, and a baking method, a spray coating method, a PVD method, a CVD method, or the like can be used.

[0064] [Oxygen electrode layer 9] The oxygen electrode layer 9 is disposed on the opposite side of the hydrogen electrode layer 6 with respect to the electrolyte layer 7. In this embodiment, since the reaction prevention layer 8 is disposed between the electrolyte layer 7 and the oxygen electrode layer 9, the oxygen electrode layer 9 is connected to the reaction prevention layer 8. If the reaction prevention layer 8 is not disposed between the electrolyte layer 7 and the oxygen electrode layer 9, the oxygen electrode layer 9 is connected to the electrolyte layer 7.

[0065] The oxygen electrode layer 9 reacts with O 2 transferred from the hydrogen electrode layer 6 through the electrolyte layer 7 in accordance with the chemical reaction of the following formula (2): 2- produces O2 from

[0066] Oxygen electrode layer 9:2O 2- →O2+4e - (2)

[0067] The oxygen electrode layer 9 is made of a porous material having oxide ion conductivity and electron conductivity. The oxygen electrode layer 9 can be made of a composite material of one or more of (La,Sr)(Co,Fe)O3, (La,Sr)FeO3, La(Ni,Fe)O3, (La,Sr)CoO3, and (Sm,Sr)CoO3 and an oxide ion conductive material (such as GDC).

[0068] The porosity of the oxygen electrode layer 9 is not particularly limited, but may be, for example, 20% to 60%. The thickness of the oxygen electrode layer 9 is not particularly limited, but may be, for example, 1 μm to 100 μm.

[0069] The method for forming the oxygen electrode layer 9 is not particularly limited, and a baking method, a spray coating method, a PVD method, a CVD method, or the like can be used.

[0070] [Flow path member 30] The flow path member 30 is joined to the second main surface 13 of the metal support 10. The flow path member 30 forms a flow path 30a between itself and the metal support 10. A source gas is supplied to the flow path 30a. The source gas supplied to the flow path 30a is supplied to the hydrogen electrode layer 6 of the cell main body 20 through each communication hole 11 of the metal support 10.

[0071] The flow path member 30 can be made of, for example, an alloy material. The flow path member 30 may be formed of the same material as the metal support 10. In this case, the flow path member 30 may be substantially integral with the metal support 10.

[0072] The flow path member 30 has a frame 31 and an interconnector 32. The frame 31 is an annular member that surrounds the side of the flow path 30a. The frame 31 is joined to the second main surface 13 of the metal support 10. The interconnector 32 is a plate-like member for electrically connecting an external power source or another electrolysis cell to the electrolysis cell 1 in series. The interconnector 32 is joined to the frame 31.

[0073] In this embodiment, the frame 31 and the interconnector 32 are separate members, but the frame 31 and the interconnector 32 may be an integrated member.

[0074] (Details of the reduction treatment of the gas diffusion layer 5) In order to impart electronic conductivity to the gas diffusion layer 5, it is necessary to reduce the NiO contained in the gas diffusion layer 5 to Ni by subjecting the gas diffusion layer 5 to a heat treatment (i.e., reduction treatment) in which a reducing gas is supplied to the gas diffusion layer 5 at high temperature.

[0075] The reduction of NiO to Ni causes a dimensional change in the gas diffusion layer 5. As a result, the electrolysis cell 1 warps in a convex shape toward the metal support 10, or the electrolysis cell 1 warps in a convex shape toward the opposite side to the metal support 10. When the electrolysis cell 1 warps toward the metal support 10, cracks are likely to occur near the centers of the hydrogen electrode layer 6 and the electrolyte layer 7 in the X-axis direction perpendicular to the Z-axis direction. Furthermore, when the electrolysis cell 1 warps toward the opposite side to the metal support 10, peeling is likely to occur between the electrolyte layer 7 and the hydrogen electrode layer 6, or between the electrolyte layer 7 and the reaction prevention layer 8.

[0076] 2 and 3 show the results of a simulation showing the relationship between the thickness of the gas diffusion layer 5 and the curvature of the electrolysis cell 1 when a reduction treatment was carried out by supplying a reducing gas at 750° C. for three hours.

[0077] The unit of the thickness of the gas diffusion layer 5 is μm. The curvature is an index showing the degree of warping of the electrolysis cell 1 in the Z-axis direction. The unit of the curvature is 1 / m. A positive curvature value means that the electrolysis cell 1 is warped toward the metal support 10, and a negative curvature value means that the electrolysis cell 1 is warped away from the metal support 10.

[0078] The simulation conditions for FIGS. 2 and 3 are as follows:

[0079] Metal support 10: Thickness 300 μm, stainless steel Gas diffusion layer 5: Thickness 50~600μm, NiO+Y2O3 Hydrogen electrode layer 6: Thickness 15μm, NiO+8YSZ Electrolyte layer 7: Thickness 8μm, 8YSZ Reaction prevention layer 8: Thickness 8μm, GDC Oxygen electrode layer 9: Thickness 15μm, LSCF

[0080] 2 shows five curves indicating the relationship between thickness and curvature when the dimensional change rate of the gas diffusion layer 5 is changed to -0.01%, -0.03%, -0.05%, -0.07%, and -0.09%. In FIG. 2, the curvature is a positive value, so the electrolysis cell 1 is warped toward the metal support 10.

[0081] 3 shows five curves indicating the relationship between thickness and curvature when the dimensional change rate of the gas diffusion layer 5 is changed to +0.01%, +0.03%, +0.05%, +0.07%, and +0.09%. In FIG. 3, the curvature is mainly a negative value, so the electrolysis cell 1 is warped toward the opposite side to the metal support 10.

[0082] As can be seen from FIGS. 2 and 3, both the thickness and the dimensional change rate of the gas diffusion layer 5 have a significant effect on the curvature (ie, warpage) of the electrolysis cell 1.

[0083] Specifically, the curvature of the electrolysis cell 1 tends to increase as the absolute value of the dimensional change rate of the gas diffusion layer 5 increases. Furthermore, in a range where the thickness of the gas diffusion layer 5 is 50 μm to 200 μm, the curvature of the electrolysis cell 1 tends to increase as the thickness increases, whereas in a range where the thickness of the gas diffusion layer 5 is more than 200 μm, the curvature of the electrolysis cell 1 tends to decrease as the thickness increases.

[0084] 2, the electrolysis cell 1 is warped toward the metal support 10, and therefore if the curvature is large, cracks are likely to occur in the hydrogen electrode layer 6 and the electrolyte layer 7, and the threshold curvature that can suppress cracks in the hydrogen electrode layer 6 and the electrolyte layer 7 is set to 0.55 (1 / m). As described above, in this embodiment, the thickness of the gas diffusion layer 5 needs to be 100 μm or more.

[0085] Therefore, in order to keep the curvature at 0.55 (1 / m) or less, if the dimensional change rate is -0.09%, the thickness of the gas diffusion layer 5 needs to be 550 μm or more, and if the dimensional change rate is -0.07%, the thickness of the gas diffusion layer 5 needs to be 380 μm or more. On the other hand, if the dimensional change rate is -0.05% or more, the curvature can be kept at 0.55 (1 / m) or less over the entire range in which the gas diffusion layer 5 has a thickness of 100 μm or more.

[0086] 3, the electrolysis cell 1 is warped toward the side opposite to the metal support 10, and therefore if the curvature is large, peeling is likely to occur in the hydrogen electrode layer 6 and the electrolyte layer 7, and the threshold curvature that can prevent peeling of the hydrogen electrode layer 6 and the electrolyte layer 7 is set to 0.40 (1 / m). As described above, the gas diffusion layer 5 needs to have a thickness of 100 μm or more.

[0087] Therefore, in order to keep the curvature at 0.40 (1 / m) or less, if the dimensional change rate is +0.09%, the thickness of the gas diffusion layer 5 needs to be more than 600 μm, and if the dimensional change rate is +0.07%, the thickness of the gas diffusion layer 5 needs to be 500 μm or more. On the other hand, if the dimensional change rate is +0.05% or less, the curvature can be kept at 0.40 (1 / m) or less over the entire range in which the gas diffusion layer 5 has a thickness of 100 μm or more.

[0088] As described above, by making the thickness of the gas diffusion layer 5 100 μm or more and making the dimensional change rate of the gas diffusion layer 5 within ±0.05% (i.e., −0.05% or more and +0.05% or less), it is possible to improve the gas diffusibility of the gas diffusion layer 5 while suppressing damage to the hydrogen electrode layer 6 and the electrolyte layer 7.

[0089] The dimensional change rate of the gas diffusion layer 5 is expressed by (ΔL / L1) × 100, where L1 is the dimension of the gas diffusion layer 5 in a non-reduced state at room temperature, L2 is the dimension of the gas diffusion layer 5 in a reduced state at room temperature, and ΔL is the amount of change, ΔL = L2 - L1.

[0090] "Dimensions" refers to the thickness of the gas diffusion layer 5, the representative length of the shape of the gas diffusion layer 5 in a planar view (the diameter in the case of a circle, the length of one side in the case of a square, and the length of the long side in the case of a rectangle), etc.

[0091] ΔL can be controlled by adjusting at least one of the average particle size ratio of NiO to the ceramic material, the volume ratio of NiO, and the volume ratio of the ceramic material. When the average particle size of NiO is R1 and the average particle size of the ceramic material is R2, the value of the average particle size ratio R2 / R1 is not particularly limited, but can be, for example, 0.1 or more and 1.5 or less. The average particle size ratio R2 / R1 is a measurement value in a non-reduced state that has not been subjected to reduction treatment.

[0092] The average particle size ratio R2 / R1 of NiO and ceramic material can be obtained by the following method. First, the surface of the gas diffusion layer 5 is polished, and then the surface of the gas diffusion layer 5 is thermally etched to clarify the grain boundaries between NiO particles and ceramic particles. Next, an SEM (scanning electron microscope) image of the surface of the gas diffusion layer 5 is obtained at a magnification that can accommodate a total of about 150 NiO particles and ceramic particles. Next, the SEM image is analyzed to determine the total area and number of all NiO particles, and the total area and number of all ceramic particles. Then, the total area of ​​all NiO particles is divided by the number of particles to calculate the average particle size R1 of NiO, and the total area of ​​all ceramic particles is divided by the number of particles to calculate the average particle size R2 of the ceramic material. Then, the average particle size ratio R2 / R1 is calculated by dividing the average particle size R2 by the average particle size R1. [Explanation of symbols]

[0093] 1 Electrolysis cell 10 Metal support 11 Communication hole 12 First main surface 13 Second main surface 20 Cell body 5 Gas diffusion layer 6 Hydrogen electrode layer 7 Electrolyte layer 8. Reaction prevention layer 9 Oxygen Polar Layer 30 Flow path member 30a Flow path

Claims

1. a metal support having a plurality of communicating holes formed on a main surface thereof; a cell body including a gas diffusion layer formed on the main surface and covering the plurality of communication holes, a hydrogen electrode layer disposed on the gas diffusion layer, an oxygen electrode layer, and an electrolyte layer disposed between the hydrogen electrode layer and the oxygen electrode layer; Equipped with The gas diffusion layer is made of NiO and a ceramic material, The thickness of the gas diffusion layer is 100 μm or more, When the dimension of the gas diffusion layer in a reduced state obtained by subjecting the gas diffusion layer to a heat treatment in a reducing atmosphere at 750° C. is L2 at room temperature, and the dimension of the gas diffusion layer in a non-reduced state that has not been subjected to the heat treatment is L1 at room temperature, the amount of change therebetween is ΔL=L2-L1, (ΔL / L1)×100 is within ±0.05%. Electrolysis cell.

2. The thickness of the gas diffusion layer is 450 μm or less.

2. The electrolysis cell of claim 1.

3. The gas diffusion layer contains yttria as the ceramic material.

3. An electrolytic cell according to claim 1 or 2.

Citation Information

Patent Citations

  • Cell, cell stack device, module, and module housing device

    WO2021221052A1